A Descriptive Case Series on Combined Education, Breast Care, and Oxytocin Massage for Lactation Support in Indonesia - Zakiyyah Putri, Sitti; Sitti Maryam Bachtiar; Suprapto (The Indonesian Institute of Science and Technology Research, 2025)
Exclusive breastfeeding during the first six months of life is essential for optimal infant growth, development, and immune protection. Despite various efforts, the prevalence of exclusive breastfeeding in Indonesia remains suboptimal, often influenced by challenges related to maternal confidence, infant latch, and effective breastfeeding techniques. This exploratory case series aimed to describe short-term changes in breastfeeding outcomes following combined interventions of education, breast care, and oxytocin massage among postpartum mothers. Using a descriptive observational case series design, four postpartum mothers experiencing early breastfeeding difficulties received structured education, breast care, and oxytocin massage interventions, administered according to standardized clinical procedures. Breastfeeding outcomes, including infant latch quality, maternal positioning skills, signs of milk ejection, and maternal confidence, were assessed before and after the interventions. Preliminary observations indicated improvements across several of these parameters. However, the study’s findings are limited by its small sample size and reliance on subjective observations. As an exploratory study, these results offer initial insights but should be interpreted with caution. Further research with larger samples, control groups, and objective evaluation tools is needed to determine the efficacy and generalizability of these interventions.